Pengaruh penambahan kitosan pada media tumbuh Beauveria bassiana (Bals.) Vuill terhadap pertumbuhan, perkembangan, dan virulensinya pada walang sangit (Leptocorisa acuta F.) - Muhammad Ainul Yaqin; Nanang Tri Haryadi (Jurnal Entomologi Indonesia, 2022)
Continuous propagation of the fungus Beauveria bassiana on artificial media will cause a decrease in its virulence. The solution offered as an alternative to maintain the virulence of the B. bassiana fungus is the addition of chitosan to the growing medium with the right concentration. This study aims to determine the effect of the addition of chitosan at several concentrations on growth, development and virulence of B. bassiana. This research was designed using a completely randomized design with 6 treatments and 4 replications. The treatments used are P0 (control), P1 (chitosan 1 mg/ml), P2 (chitosan 2 mg/ml), P3 (chitosan 3 mg/ml), P4 (chitosan 4 mg/ml), and P5 (chitosan 5 mg/ml). The results showed that chitosan affected the growth and development of B. bassiana fungi, as seen in parameters of colony diameter and conidia viability. The highest colony diameter occurred in the P1 treatment that was 8.34 cm and the highest conidia viability also occurred in the P1 treatment which was 85.26%. The effect of chitosan on B. bassiana virulence can be seen in the parameters of mortality, mycosis, and mummification. The addition of a chitosan concentration of 1 mg/ml in the fungal growth medium has a good effect on the growth and virulence of B. bassiana.